ANALISIS KOMPETENSI GURU PENDIDIKAN PANCASILA DALAM PENGGUNAAN TEKNOLOGI DIGITAL UNTUK PEMBUATAN MEDIA PEMBELAJARAN YANG MENARIK DI UPT SMP NEGERI 6 MEDAN TAHUN PEMBELAJARAN 2025/2026 - Limra, Limra G.M Nababan; Liber Siagian, Liber Siagian; Arief Wahyudi, Arief Wahyudi; Fazli Rachman, Fazli Rachman; Jamaludin, Jamaludin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine how the competency analysis of Pancasila Education Teachers in the use of digital technology to create interesting learning media at UPT SMP Negeri 6 Medan in the 2025/2026 Academic Year. The problems found in the field where teachers still carry out monotonous learning processes in class and the use of digital technology to create interesting learning media is not optimal for the needs of the teaching and learning process. The research method used in this study is the mixed methods method or a mixed method of the Exploratory sequential design type by collecting data through observation, interviews, questionnaires and documentation. The location of this research is at UPT SMP Negeri 6 Medan, which is located at Jl. Bahagia No. 42, Teladan Timur Village, Medan Kota District, Medan City, North Sumatra Province. In this study the informants used were 35 people consisting of 2 Pancasila Education teachers of grade IX and 33 grade IX students. The research results indicate that ninth-grade Pancasila Education teachers possess excellent competency in the use of digital technology to create engaging learning media. This is supported by student assessments of the four competencies, with 89.09% being categorized as excellent. Furthermore, data on the creation and selection of engaging learning media showed a 91.26% categorization as excellent. Teachers understand how to use and utilize technology and media platforms through continuous independent learning and training, further enhancing their understanding.